PENGARUH INSENTIF DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. DUTA EXPO LABUHANBATURANTAUPRAPAT - Elvina, Elvina (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2018)
Sampling method using saturated sampling (the census) on the performance of the employees on PT Duta Expo Labuhanbatu as much as 40 people. Testing the hypothesis using the double linier regression, with test launches ( test F), and partially (test t) to know the influence of the independent variables against the dependent varaibel on the level of trust 95% or Î± = 0.05. The results of the analysis showed that the influence of the structure of incentives and competence of employees performance with the results of the regression Y = 7,544 0,050 X1 1,369 X2,which means that without the existence of incentives and competence, the performance of the employees will remain with the value of 7,544. While the value of RÂ² = 60,20% and the rest of the other variables is not influenced involved in this research.